The Relationship between Workload and Psychological Fatigue (Burnout) - Waldani, Dina; Gustina Indriati (RADINKA JOURNAL OF HEALTH SCIENCE, 2023)
Workload is the amount of work that must be carried by a position or organizational unit and is the product of the volume of work and the time norm. Researchers conducted a pre-survey of 10 employees at Bank BTN KC Padang in the Teller and Marketing section, 8 employees who were pre-survey respondents answered "Yes" or 80% experienced workload with psychological fatigue (burnout), while 2 employees who were pre-survey respondents answered "No" or 20% did not experience workload with psychological fatigue (burnout). The research design is quantitative descriptive. The population is 51 people, and all populations are sampled with a total of 51 people. In this study, the authors used the Maslach Burnout Inventory (MBI) scale, and the authors used a workload scale based on the dimensions of the Nasa-Task Load Index (NASA-TLX). The results of this study indicate that there is a significant effect of workload on burnout. In this study it was found that there was an effect of the workload variable on the level of frustration on burnout which resulted in employees feeling insecure, hopeless and irritable. Thus it is expected that superiors pay more attention to the intimacy of fellow employees and build a sense of solidarity to avoid the things above and pay attention to the safety and health of employees to build a sense of security at work.